PENGARUH MOTIVASI KARIER, MOTIVASI EKONOMI, DAN MOTIVASI GELAR TERHADAP MINAT MAHASISWA AKUNTANSI MENGIKUTI PENDIDIKAN PROFESI AKUNTANSI - Kurniawan, Adhitya Reza; Zulaikha, Zulaikha (Diponegoro Journal of Accounting, 2015)
Accounting profession education (PPA) established to graduate a professional accountantin the future. The PPA program will not produce a professional accountants which acceptable by the company if the students did not have high motivation to study accounting in professional way . Based on this backround the objectives of this research is to analyzed if carrier motivation, economic motivation, and title motivation have some effects on accounting students interest to enroll in PPA program at Economics and Business Faculty of Diponegoro University.The sample of this research using direct survey method that distributed to 100 respondents of accounting students in Economics and Business Faculty of Diponegoro University that has been finished auditing subject. Data in this research were obtained using questionnaires and were analyzed. The hypothesis testing in this research using multiple regression analysis with SPSS release 19.The result of this analysis showed that career motivation and title motivation significantly affect for accounting students interest to enroll in PPA program. It indicates that a self motivation for having an accountant title is more competitive than just graduates from accounting under gradute program, so they become more professional and get better carieer in accounting. On the other side, economic motivation has no significant effect for accounting students interest in PPA. This probably happen because there is a point of view that having an accountant title and a good carieer can improve their economic welfare.